Positive psychological assessment a handbook of models and measures - Lopez, Shane J. 1970-2016 (American Psychological Assoc., 2003)
This handbook is a primer for practitioners and researchers striving to incorporate the assessment of human strengths, resources, and fulfillment into their work. Contributors aptly examine the scientific underpinnings and practical applications of measures of hope, optimism, self-efficacy, problem solving, locus of control, creativity, wisdom, courage, positive emotion, self-esteem, emotional intelligence, empathy, attachment, forgiveness, humor, gratitude, faith, morality, and quality of life. Vocational and multicultural applications of positive psychological assessment are also discussed, as is the measurement of contextual variables that may facilitate the development or enhancement of human strength. The variety of perspectives offered will be immensely helpful to readers who wish to incorporate balance into their assessments and research through the integration of theoretically grounded positive measures. (PsycINFO Database Record (c) 2004 APA, all rights reserved).
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Psychologie positive; Psychologische tests; Test psychologique; Tests psychologiques; Évaluation psychologique; Attitude; Models, Psychological; Personality Assessment; Psychological Tests; Psychological tests; Test; Positives Denken; Wertorientierung; Einstellungsmessung; Psychometrie; Aufsatzsammlung